Dr. R. S. Hazuria: A Life of Medicine, Compassion and Healing - Dr Yamini Malhotra (International Journal of Creative and Open Research in Engineering and Management, 2026)
Dr. Raminder Singh Hazuria represents a distinctive model of Indian medical practice in which professional competence, continuity of care, personal humility, and profound compassion toward patients are closely intertwined [1]. A physician identified in official international medical directories with expertise in internal medicine and cardiology, Dr. Hazuria served as a general physician, cardiologist, and diabetologist whose influence extended far beyond the conventional doctor–patient relationship [1,2]. The present study examines Dr. Hazuria’s professional identity, his contributions as a cardiologist and internal medicine specialist, the noble philosophy of healing associated with him, the significance of long-term intergenerational patient relationships, and the ethical and spiritual dimensions attributed to his medical practice [1]. Independent documentary sources corroborate his identification as Raminder Singh Hazuria, a physician associated with internal medicine and cardiology in New Delhi, and his membership in the Cardiological Society of India [2–4]. The study argues that the significance of Dr. Hazuria’s career lies not only in his specialized expertise in cardiovascular medicine but also in the humanistic model of medicine represented by his long-standing commitment to individual patients and community well-being [1]. Keywords: Dr. R.S. Hazuria, Raminder Singh Hazuria, Cardiology, Internal medicine, Diabetology, Medical humanities, Doctor–patient relationship, Medical ethics, Compassionate Healthcare.